Historians on Contemporary Times. The Year of Dangerous Change (2010) according to Georges Mink and Timothy Snyd - Fiećko, Jerzy (Poznańskie Studia Slawistyczne, 2019)
The author analyses the ways of depicting contemporary times in two monographs written by renown scholars: La Pologne au coeur de l’Europe. De 1914 à aujourd’hui, histoire politique et conflits de mémoire (Poland at the heart of Europe. From 1914 to the present day. Political history and conflicts of memory) and The Road to Unfreedom. Russia, Europe, America by Timothy Snyder. A particularly important date here is 2010, the year of the Smolensk air disaster, which in Poland gave rise to many false myths and manipulations of facts (described by both authors). Snyder chooses this year as a symbolic turning point within the global process of shifting from the mindset of “inevitability” towards the mindset of “eternity”. The second main characteristic of this way of thinking and acting is that truth and facts are replaced in the public discourse with fake news, fabrications, creating social divisions and stirring hostile emotions.